Ligand 2018
DOI: 10.5772/intechopen.73502
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Silylphosphine Ligands for Transition Metal Complexation

Abstract: In this chapter, a review throughout the literature on the chemistry of multidentate silylphosphines is presented. The incorporation of P and Si functionalities in cooperation in a single ligand backbone is exceptionally versatile, and examples of this rich chemistry stemming from the works of many research groups around the world are herein provided. The ligand systems can be flexible or rigid and incorporate varying numbers of P, Si and even other atoms. Exceptional ligand-metal systems are discussed in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…22,25 As part of our research program aimed at developing organometallic complexes for catalytic and environmental applications, we have synthesized a series of modularly variable semiflexible pincer-like ligand architectures, silylphosphine ligands, with varying electronic and steric properties. 33,34 We have proved that the tridentate ligand [PhP(o-C 6 H 4 CH 2 Si i Pr 2 H) 2 ] is able to stabilize coordinatively unsaturated 14-electron Ir(III) centers, 35 namely, [XIr{κ 3 (P,Si,Si)-PhP(o-C 6 H 4 CH 2 Si i Pr 2 ) 2 }] (X = halogen, Me, CH 2 SiMe 3 , etc.). We proposed that the incorporation of some of these complexes into MOF material NU-1000 would enhance the catalytic activity and the gas adsorption properties of the MOF due to the availability of additional coordination sites at the Ir metal to host SO 2 in either η 1 or η 2 coordination modes, the electronic stabilization of Ir by the strong sigma donor ligand, and even the possibility to free an additional coordination site.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22,25 As part of our research program aimed at developing organometallic complexes for catalytic and environmental applications, we have synthesized a series of modularly variable semiflexible pincer-like ligand architectures, silylphosphine ligands, with varying electronic and steric properties. 33,34 We have proved that the tridentate ligand [PhP(o-C 6 H 4 CH 2 Si i Pr 2 H) 2 ] is able to stabilize coordinatively unsaturated 14-electron Ir(III) centers, 35 namely, [XIr{κ 3 (P,Si,Si)-PhP(o-C 6 H 4 CH 2 Si i Pr 2 ) 2 }] (X = halogen, Me, CH 2 SiMe 3 , etc.). We proposed that the incorporation of some of these complexes into MOF material NU-1000 would enhance the catalytic activity and the gas adsorption properties of the MOF due to the availability of additional coordination sites at the Ir metal to host SO 2 in either η 1 or η 2 coordination modes, the electronic stabilization of Ir by the strong sigma donor ligand, and even the possibility to free an additional coordination site.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The dimer coordinated with the Et2dtc• radical produced involves the reaction of initial complex and intermediate; accompanied by microseconds the dithiocarbamate radicals, which reunited to produce a tetranuclear cluster. These turned out to be challenging on stationary photolysis when looking at the mechanism of photochemical transformations of the Cu(Et2dtc)2 complex [81,82].…”
Section: Molecular Precursor Complexesmentioning
confidence: 99%
“…The advantage of these over traditional organometallics is the absence of toxic metals like lead alkyls or H 2 S. They are easy to fabricate and stable for months and give high yields with thermolysis. The decomposition of Pb (S 2 CNEt 2 ) 2 complex in tri-n-octyl phosphine oxide produces cube-shaped quantum dots [82]. Similarly, Cheon et al produced rod-based star-shapes, cubes and highly faceted and truncated octahedrons of different structures with the same precursor (Figure 7) [63].…”
Section: Molecular Precursor Complexesmentioning
confidence: 99%
“… It was later shown that these ethylene- and propylene-bridged ligands I′ are rather flexible, rendering the metal complexes kinetically labile, which tentatively precluded any applications in catalysis. , Thus, the more rigid bis­( o -phosphinophenyl)­silanes [R 2 P­( o -C 6 H 4 )] 2 SiMeH ( II ) have been frequently used in reactions with metals, such Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, and Au, which in most cases (except Cu, Au) provided stable pincer complexes with the related ligand II′ . The ethylene-bridged pincer ligands I′ ( n = 2) and II′ are expected to create bonding situations with similar P–M–P bite angles due to the same number of bridging carbon atoms. Many of these pincer complexes were formed via oxidative addition across the Si–H bonds and feature activated M–H bonds and have found diverse applications in catalysis, including for instance the reduction of carbon dioxide or transfer hydrogenation reactions. For the coinage metals Cu and Au, no oxidative addition was observed. …”
Section: Introductionmentioning
confidence: 99%